Comparative polysomnography parameters between narcolepsy type 1/type 2 and idiopathic hypersomnia: A systematic review and meta-analysis. (June 2022) - Zhang, Ye; Ren, Rong; Yang, Linghui; Zhang, Haipeng; Shi, Yuan; Vitiello, Michael V.; Tang, Xiangdong; Sanford, Larry D.
Summary: A meta-analysis exploring polysomnography (PSG) differences between narcolepsy type 1 (NT1)/type 2 (NT2) and idiopathic hypersomnia (IH), particularly one that stratifies the analysis by IH with and without long sleep time (LST), could provide information useful for appropriately re-classifying the central disorders of hypersomnolence. An electronic literature search was conducted in EMBASE, MEDLINE, All EBM databases, CINAHL, and PsycINFO inception to May 2021. Meta-analysis of 26 studies revealed that the effect sizes of differences in some PSG parameters between NT1 and IH were different from those between NT2 and IH. Specifically, there were significant increases in wake time after sleep onset (WASO), arousal index (AI), and N1 percentage, and significant decreases in sleep efficiency, sleep latency, and N2 percentage in NT1 compared with IH, but no differences for these sleep parameters between NT2 and IH. With the exception of rapid eye movement (REM) sleep percentage and REM latency, there were no significant differences in other PSG variables between NT2 and IH without LST. The findings suggest that, NT1, rather than NT2, showed shallower and more fragmented sleep compared with IH. Sleep macrostructure features are very similar between NT2 and IH without LST.